Do longus capitis and colli really stabilise the cervical spine? A study of their fascicular anatomy and peak force capabilities. (December 2017) - Kennedy, Ewan; Albert, Michael; Nicholson, Helen
Abstract: Background: Longus capitis and colli are proposed to play a role in stabilising the cervical spine, targeted in clinical and research practice with cranio-cervical flexion. However, it is not clear if these muscles are anatomically or biomechanically suited to a stabilising role. Objectives: To describe the fascicular morphology of the longus capitis and colli, and estimate their peak force generating capabilities across the individual cervical motion segments. Study design: Biomechanical force modelling based on anatomical data. Methods: Three-part design including cadaveric dissection (n = 7), in vivo MRI muscle volume calculation from serial slices in young healthy volunteers (n = 6), and biomechanical modelling of the peak force generating capacities based on computed tomography scans of the head and neck. Results: Longus capitis and colli are small muscles spanning multiple cervical motion segments. Bilateral peak flexion torque estimates were higher in the upper cervical spine (0.5 Nm), and unlikely to affect motion below the level of C5 (<0.2 Nm). Peak shear estimates were negligible (<20 N), while peak compression estimates were small (<80 N). Conclusions: These data highlight the complex anatomy and small force capacity of longus capitis and colli, and have implications for their function. In particular, the small peak compression forces indicate that these muscles have a limited capacity to contribute to cervical stability via traditional mechanisms. This implies that the mechanism(s) by which cranio-cervical flexion exercises produce clinical benefits is worth exploring further. Highlights: Longus capitis and colli are small muscles with complex fascicle arrangements. The longus muscles are capable of generating only small peak forces. The capacity for the longus muscles to contribute to cervical stability is limited. These findings have implications for exercises targeting the longus muscles.